NUTRIENT PROFilE OF POND WATER IN NORTH-EASTERN STATE OF TRIPURA AND IMPACT OF WATER ACIDITY ON AQUACUlTURE PRODUCTIVITY
Physico-chemical parameters of 31 fish pond water samples of Tripura were studied to ascertain the nutrient profile of acidic soil zone and the impact of water acidity towards aquaculture productivity. The pH was acidic (mean 6.63±0.44) with high Fe (mean1.04±0.40 mgf1 ) and AI mean 2.67±2.41 mgf1 ) contents. These were mostly responsible for pond water acidity and poor productivity with low nitrogen, phosphate and total alkalinity. The study also showed strong negative relationship between water pH and redox potential R2 =0.5251). However, pH was positively significant with electrical conductivity. The roles of redox potential and electrical conductivity in water acidity were found highly important. Available calcimn content was also found low mean 2.91±2.96 mgf1 ). Elevating level of pH of pond water could be the possible management practices in acidic water so that such unproductive water might be productive enough with higher phosphate and nitrogen levels for better biological production. Keywords: Tripura, red acidic soil, acidic water, pH, redox potential. , journal=Journal of Indian Fisheries Association, author=Datta, M. K. and Saha, Ratan K. and Dhanze, J. R. and Prakash, Chandra and Singh Kohli, M.P. and Saharan, N., year=2008, month=Dec.